2016
DOI: 10.1155/2016/9237127
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Cluster Analysis in PathogenicEscherichia coliIsolates Producing Different CDT Types

Abstract: Diarrheagenic and uropathogenic E. coli types are mainly characterized by the expression of distinctive bacterial virulent factors. stx1, stx2 (Shiga toxins), and cdt (cytolethal distending toxin) genes have been acquired by horizontal gene transfer. Some virulent genes such as espP (serine protease), etpD (part of secretion pathway), and katP (catalase-peroxidase), or sfpA gene (Sfp fimbriae), are on plasmids and the others like fliC (flagellin) and the fimH gene (fimbriae type-I) are located on chromosome. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Most E. coli strains are harmless and are important part of healthy human and animal intestinal tracts. However, some strains of E. coli have acquired virulence attributes and are called pathogenic E. coli (Hessain et al, 2013;Javadi et al, 2016). Pathogenic E. coli are categorized into six pathotypes (Raji et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most E. coli strains are harmless and are important part of healthy human and animal intestinal tracts. However, some strains of E. coli have acquired virulence attributes and are called pathogenic E. coli (Hessain et al, 2013;Javadi et al, 2016). Pathogenic E. coli are categorized into six pathotypes (Raji et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This evidence further confirms that horizontal gene transfer could occur among pathogenic strains. Moreover, findings indicate that CDT-producing strains may have originated from a common ancestor during their evolution by HGT, and they departed from each other [17].…”
Section: Diversity Of E Coli Strainsmentioning
confidence: 95%
“…cdt-IV operon of strain 28C is flanked on both sides by prophage-related ORFs that was indicated by a DNA homology search and it encodes putative prophage-related proteins. Phage putative proteins include a lambdoid prophage hostspecificity protein (orf1), a Lom-like protein (orf2), a putative tail fiber protein (orf3), a putative CP-933-like protease (rorf1), and a putative OmpT-like outer membrane protease (rorf2) [17]. The genome sequence of APECO1 strain revealed that the cdt-IV operon is framed by two prophages and pathogenicity island-associated DNA sequences, including integrase and tRNA genes.…”
Section: Cytolethal Distending Toxins (Cdts)mentioning
confidence: 99%
See 2 more Smart Citations